Epidemiology of Darier's disease in Slovenia - Godić, Aleksandar (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Aim: To present a retrospective and prospective epidemiological and clinical study on Darier disease in Slovenia. Results: Data on 77 DD patients was collected in the period 1973 to 2003 from the major dermatological departmentsand outpatient units in Slovenia. The prevalence of Darier disease in Slovenia is calculated at 3.8/100000 inhabitants. The ratio of affected/unaffected family members is 0.355. The comparison of two groups of DD patients (younger and older than 19 years) for the onset of the disease didnot differ significantly although in two thirds of patients DD appeared forthe first time before the age of 19 years. Conclusion: The epidemiological and clinical data on Darier's disease in Slovenia conform to similar reports with the exception of the higher prevalence of the disease in Slovenia. UV radiation seems to be an important triggering factor and therefore it is reasonable to advise DD patients to avoid sun exposure.
Keywords: Age Of Onset; dermatologija; Diagnosis; epidemiologija; Epidemiology; keratodermija; Keratosis Follicularis; Keratoza folikularna; Pathology; Prevalenca; Prevalence; Starost pri obolevnosti